Analisis Routing Protokol Optimized Link State Routing (OLSR) Pada Raspberry Pi - Ulfa Septilia Permatasari; Indrastanti Ratna Widiasari (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2019)
Optimized Link State Routing (OLSR)is one of the two standard for mesh networks. OLSR is a link state routing protocol, which use hallo message and topology control (TC) to determine the link state information across the mobile ad-hoc network. OLSR is widely used in the wireless mesh network. Raspberry Pi is a mini computer which can be used as a node router to replace the function of a router in a wireless mesh network. In this research, Raspberry Pi is used as a router nodes to determine the performance of routing protocol OLSR. The parameters used to measure its performance is self-configure time, self-healing and bandwidth usage. The test results showed that the use of routing protocols OLSR on the Raspberry Pi in a wireless mesh network proved able to repair itself if there is a problem on the network since it has ability to self-configure and self-healing.